Effect of black soldier fly (Hermetia illucens L.) larvae meal on growth performance, carcass characteristics, meat quality, and cecal microbiota in broiler chickens - Saidani, Mariem; Dabbou, Sihem; Ben Larbi, Manel; Belhadj Slimen, Imen; Fraihi, Wael; Arbi, Tarek; Amraoui, Marouen; M’Hamdi, Naceur (Frontiers in Animal Science, 2025)
The current study was conducted to evaluate the effects of Black Soldier Fly (BSF) larvae meal in broiler chicken diets on growth performance, carcass characteristics, meat quality, and cecal microbiota. 300 unsexed Arbor Acres chicks were divided into two treatment groups, each with six replicates of 25 chicks. The experimental group was fed a diet in which soybean meal was partially substituted with 5% BSF larvae meal during the starter phase (1–14 days) and 10% during the grower phase (15–28 days). The finisher period is a BSF-free diet. Results showed no significant difference in growth performance between the experimental and control groups, except for a higher average weight in the second week (P=0.016). A significant difference was observed in the yield of hot eviscerated carcasses (P=0.001), while no significant differences were found in meat quality parameters, including pH, myoglobin, water-holding capacity, cooking loss, chemical composition (dry matter, ash, and ether extract), and bacterial counts such as total aerobic mesophilic flora, Enterobacteriaceae and E. coli. The inclusion of BSF larvae meal reduced harmful bacteria such as Enterobacteriaceae and increased beneficial bacteria such as Lactobacillus spp., in the chicken’s cecal microbiota. These findings suggest that BSF larvae provide health benefits in meal forms, supporting their potential as a viable and sustainable alternative protein source to partially replace soybean meal in broiler diets.